2020
DOI: 10.3390/ijms21030932
|View full text |Cite
|
Sign up to set email alerts
|

Lack of PKCθ Promotes Regenerative Ability of Muscle Stem Cells in Chronic Muscle Injury

Abstract: Duchenne muscular dystrophy (DMD) is a genetic disease characterized by muscle wasting and chronic inflammation, leading to impaired satellite cells (SCs) function and exhaustion of their regenerative capacity. We previously showed that lack of PKCθ in mdx mice, a mouse model of DMD, reduces muscle wasting and inflammation, and improves muscle regeneration and performance at early stages of the disease. In this study, we show that muscle regeneration is boosted, and fibrosis reduced in mdxθ−/− mice, even at ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…Frozen heart ventricles were cut into 8 μm sections and stored at −20 °C until use. Histochemistry and immunofluorescence analyses were performed as previously described [ 35 , 36 ]. Briefly, for histological analysis, the sections were stained with hematoxylin/eosin or with Sirius red/picric acid (both from Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Frozen heart ventricles were cut into 8 μm sections and stored at −20 °C until use. Histochemistry and immunofluorescence analyses were performed as previously described [ 35 , 36 ]. Briefly, for histological analysis, the sections were stained with hematoxylin/eosin or with Sirius red/picric acid (both from Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This beneficial effect was mainly due to the inhibition of PKCθ in T cells, which leads to reduced inflammation [10][11][12]. Interestingly, we also found that lack of PKCθ promotes muscle repair in dystrophic mice, even at advanced stages of the disease, supporting SCs survival and maintenance [13]. However, whether this effect was due to reduced inflammation or to a direct role of PKCθ on SCs activity, or both, was still unclear.…”
Section: Introductionmentioning
confidence: 53%
“…Acute muscle injury was induced the day before SC transplantation. To induce muscle injury tibialis muscles were injected with 0.01 ml of Cardiotoxin from Naja Pallida (10 μM) (Latoxan ZA, Les Auréats, Fr), using a 30 Gauge micro-syringe [23][24][25][26].…”
Section: Sc Transplantationmentioning
confidence: 99%